A simple, reliable method to determine the mean gait speed using heel markers on a treadmill. Issue 8 (11th June 2017) - Souza, Gustavo Souto de Sá e; Rodrigues, Fábio Barbosa; Andrade, Adriano O.; Vieira, Marcus Fraga
Abstract: Gait speed is an essential parameter of gait analysis. Our study proposed a simple and accurate method to extract a mean gait speed during walking on a treadmill using only kinematic data from markers placed on the heels of the participants' feet. This method provided an attractive, simple method that remains resistant to errors in treadmill calibration. In addition, this method required only two markers, since heel markers are essential to gait analysis, and the proposed method is robust enough to differentiate among various gait speeds (mean error <1%).